Integrated metabolomics and proteomics analysis reveals the accumulation mechanism of bioactive components in Polygonatum odoratum - Liang, Shuang; Zhao, Yang; Luo, Zhaohui; Liu, Junchen; Jiang, Xicen; Yang, Bingxian; Zhang, Lin; Fu, Hongwei; Zhong, Zhuoheng (Frontiers in Plant Science, 2024)
Polygonatum odoratum (MILL.) DRUCE is rich in bioactive components with high medicinal value. To maximize the clinical benefits, it is of great significance to efficiently extract key bioactive components from appropriate growth stages in which they are most abundant. In this study, we analyzed the changes of metabolite accumulation and protein expression in P. odoratum rhizomes at different growth stages using targeted metabolomics combined with proteomics, and identified a total of 1,237 differentially abundant metabolites (DAMs). Flavonoids accumulated most in winter, and the biosynthesis pathways associated with flavonoids, isoflavonoids, flavones and flavonols exhibited significant differentially expressed proteins (DEPs).Among them, PGT, FLS, CYP75B1, HIDH, IF7MAT, and UFT73C6 were positively correlated with flavonoid accumulation. Steroid saponins accumulated most in spring, and the biosynthetic pathways of steroid and brassinosteroid biosynthesis exhibited DEPs. Among them, FDFT1, TM7SF2, DHCR7, CAS1, and 3BETAHSDD were positively correlated with steroidal saponin accumulation. In summary, these results revealed the accumulation of secondary metabolites P. odoratum in different growth stages, which can provide an effective reference for the extraction of specific bioactive components and the study of their regulatory mechanisms.